The Use of REACT Strategy for the Incorporation of the Context of Physics into the Teaching English to the Physics English Prep Students - ÖZBAY, ALİ SÜKRÜ and KAYAOGLU, MUSTAFA NACI (Journal of History Culture and Art Research, 2015)
The Use of REACT Strategy for the Incorporation of the Context of Physics into the Teaching English to the Physics English Prep Students Abstract The present study explores department of Physics prep students’ (department of Physics students attending English preparatory program) relative performance in English grammar by the use of contextual learning materials in the actual classroom instruction based on the contextual learning theory. Thus, the purpose of this study is to investigate the effect of teaching grammar in physics context for the physics prep students to increase their interests in learning English. Another primary goal of the study is to evaluate the teaching activities which are developed in accordance with the REACT (relating, experiencing, applying, cooperating and transferring) strategy in context based approach. The study was with 25 students of Physics at an English prep-school in Turkey. With the aim of determining the effect of contextual teaching materials, sample lessons based on the contextual knowledge and the target grammar points were made. Following the lessons, a structured interview was delivered to the five of the participants. One result is that the incorporation of REACT strategy into the teaching of English to the Physics students proved to be useful for the learners who took part in the study, adding that relating, experiencing, applying, cooperating and transferring the knowledge respectively helped them use and retain the knowledge far more than the traditional classroom teaching methods in grammar teaching. Another specific outcome of the overall findings is that students were able to establish connections between what they learn and how that knowledge can be utilized in physics, which, in turn, has increased their motivation to a higher level.